Modelo de desarrollo estratégico integral a partir de los recursos disponibles en la región Amazonas - Merma Cruz, Walter (2011)
The study there proposes a model of strategic integral development to stimulate the competitiveness of the Region Amazon; It is an investigation propositional, the followed methodology was initially to diagnose by means of indicators and the analysis FODA, the reality of the economic - productive sectors of the region: agriculturalist, rancher, fishing boat, mining, forest, industrial and tourist; the results indicate us that it fails to the producers of the different sectors to organize, are not competitive, scanty utilization exists to the available resources, available because one uses the factors traditions of production (land, work and the capital);as offer there is formulated an organization articulated between the private and public sector with systemic approach, to create a system of organized and competitive production with new technologies and to take advantage as strength of the biodiversity of the available resources; with a vision and mission to face the challenges before world factors that influence in the present century: the globalization and the liberalization of the trade on the world markets, the growth of the population and the urbanization, the biotechnology, the new technologies of the information and the communications, the preferences of the consumer, the environment and the governmental policies. One concludes that the strategic aims are: to promote the utilization of the resources of the region; to promote and to strengthen the associativity, competitiveness and inter-agency integration; strategy of development of competitive and sustainable products; generalization of results of the pilot centers and experimentation, sustained in three backbones: social, economic and environmental joint of policies; quality of life of agreement to cultural and intercultural diversity; viability and economic, social and ecological sustainability of the economic activities.